2022
DOI: 10.3389/fpubh.2022.1047501
|View full text |Cite
|
Sign up to set email alerts
|

Association between BMI and health-related physical fitness: A cross-sectional study in Chinese high school students

Abstract: BackgroundExisting studies reporting on the levels of physical fitness among high school students use relatively few fitness tests for indicators of physical fitness, thus, incomprehensively evaluating the levels of physical fitness. Therefore, this study investigated the relationship between body mass index (BMI) and physical fitness index (PFI) by investigating five physical fitness indicators and calculating PHI.MethodAnthropometric measurements and indicators from five measures of physical fitness (50-m sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…The best predictor for COD also appears to be BMI. Thus, our results are consistent with those of previous studies ( Campa et al, 2019 ; Chen et al, 2020 ; Qin et al, 2022 ). However, discrepancies remain between studies, as some have identified the RPI as the best predictor of COD ( Silva et al, 2016 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The best predictor for COD also appears to be BMI. Thus, our results are consistent with those of previous studies ( Campa et al, 2019 ; Chen et al, 2020 ; Qin et al, 2022 ). However, discrepancies remain between studies, as some have identified the RPI as the best predictor of COD ( Silva et al, 2016 ).…”
Section: Discussionsupporting
confidence: 94%
“…BMI has been widely used to quantify body fat and identify people who are overweight ( Qin et al, 2022 ) which have negative consequences for the health of children (e.g., dyslipidemia, arterial stiffness, and less cardio-respiratory capacity) ( Vaara et al, 2013 ; Abdelkarim et al, 2020 ) and adults (e.g., risk of heart attack) ( Jafari et al, 2019 ). Several studies have identified that a high BMI is related to poor cardiorespiratory fitness and vertical jump ( Qin et al, 2022 ; Manzano-Carrasco et al, 2023 ), which is linked to effects by the kind of sport done on physical fitness ( Tahira, 2021 ). In this sense, regular sport participation could be a great strategy to increase fitness and combat the consequences of high BMI ( Tahira, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These ndings are consistent with other studies conducted in various geographic regions of the world, which have shown quadratic (non-linear) relationships, clearly re ecting that schoolchildren categorized as underweight and overweight according to BMI induce negative effects on physical tness levels in children and adolescents [17,19,20,24] On the contrary, in the normal BMI category, the best results in HJ were observed in schoolchildren of both sexes.…”
Section: Discussionsupporting
confidence: 91%
“…During the period 2000-2019, the BMI of boys and girls in all age groups increased and the increase accelerated, especially in those aged 16-18 years. It has been shown that both higher and lower BMI can have a detrimental effect on physical fitness 22,59 . Overweight and obesity individuals tend to perform less physical activity, have longer screen time, consume more calories 60 and have a substantial decrease in physical activity.…”
Section: Discussionmentioning
confidence: 99%